Artwork Interpretations in Old and Contemporary Epic Iranian Miniatures - Pourmokhtar, Sediqeh; Afshari, Morteza (Journal of History Culture and Art Research, 2019)
Artwork interpretation in a simple word is an explanation of the meaning of art. The audiences play an important role in art and forms one of the three vertices of artwork triangle: artist, artwork and audience. If we consider artwork as a process, the audiences are the outcome of the work and is the one that created for and to be seen by them. Therefore, feedbacks or interpretations and readings of them have an important place in art critique. Iran's miniatures in different eras have experienced a variety of audiences from kings to ordinary people that affect this art. Therefore, it is expected that different kinds of interpretations have been observed. The research carried out through descriptive-analytical method, by comparing old and contemporary Iranian epic miniatures seeking to answer the question of what are the kinds of artwork interpretation in old and contemporary Iranian epic miniatures? The findings of this research shows that old paintings have created interpretations based on the author's intention and contemporary painting with a hermeneutical approach made multiple interpretations of the artworks.